ĐIỀU TRA BỆNH HẠI SAU THU HOẠCH TRÊN GIỐNG CHUỐI TIÊU HỒNG (Musa acuminata) VÀ CHUỐI NAM MỸ (Musa paradisiaca) Ở VIỆT NAM - Phan, Hồ Bảo Linh; Nguyễn, Duy Tới; Nguyễn, Thị Hải; Lại, Tiến Dũng; Đinh, Thuý Hằng; Nguyễn, Thị Hiếu Thu (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SURVEYING POSTHARVEST DISEASES ON THE Tieu hong (Musa acuminata) AND THE SOUTH-AMERICAN (Musa paradisiaca) BANANA CULTIVARS IN VIETNAMThe survey implemented in the 2021 winter season on the Tieu hong banana cultivar (Musa acuminata) grown in Phu Tho and Hung Yen provinces showed that the most severe diseases were fruit rot and fruit spot with infection rates of 79.1% and 75.5%, respectively. Peel cracking and end rot (cigar rot) were also recorded at less than 5.0%. Fruit spot was the main disease that affected the South-American banana cultivar (Musa paradisiaca) during the 2022 spring-summer season in Gia Lai province.Of the 24 fungal and 37 bacterial strains isolated from the disease samples collected during the investigation and tested for their pathogenicity via artificial infection on healthy bananas, only 17 fungal strains showed the ability of lesion formation of which 4 strains caused typical symptoms of the fruit rot disease. There was not a single bacterial strain ascertained as phytopathogen indicating that fungi were the primary agents of post-harvest diseases on bananas. These four fungal strains were taxonomically characterized based on their morphology (colony and spore), comparative analysis of the ITS sequences of the 18S rDNA gene, and were then identified as Corynespora torulosa B2B, Microdochium colombiense B6, Fusarium circinatum B13F, and Aspergillus niger GL2.1. The ITS sequences of these strains were deposited to GenBank under the accession numbers OP855524, OP855525, OP855526, and OP855527, respectively.